Age-related Mitochondrial DNA Deletions Produce Fusion Peptides in Mice - Ryhan, Md. Ayub; Chowdhury, Md. Miraj Kobad (Engineering International, 2018)
Deletions in mitochondrial DNA occur from oxidative stress generated during physiological processes. Such deletions have been associated with ageing, cancer, and neurodegeneration. In this study, the outcome of mtDNA deletions has been investigated to justify the physiological effect of such mtDNA deletion. For this, five established and two predicted age-related murine mtDNA deletions were analyzed for fusion peptide. Three out of the five established deletions and all the predicted deletions produced fusion proteins like COXIII-ND5, ND3-ND5, ATP6-ND5, and ND5-CYTB. Interestingly, we have observed that the partners of these fusion proteins are from different complexes. Thereby, these fusion proteins can produce chimeric complexes that could bypass the usual electron transport system and could make short-circuit across the mitochondrial membrane. Such event can provoke more oxidative stress leading to further accumulation of mtDNA damage and apoptosis.